PTU-034 Endoscopic Retrograde Cholagiopancreatography in the Elderly: Procedures and Complications at a District general Hospital. (4th June 2013) - Alexakis, C; Gupta, S; Mendall, M
Abstract : Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) has previously been demonstrated to be a safe and effective procedure in the elderly. The aim of this study was to assess whether similar safety data for this procedure was reproducible at a district general hospital. Methods: All patients undergoing first time ERCP between January 2007 and December 2008 were included. Data collection was partially incomplete as some procedure records were missing. Study variables included age, sex, indications, complications, and in-hospital mortality. Statistical analysis was performed to address differences in complication rates between the elderly (>80 years, Group A) and non-elderly (<80 years, Group B) patients. Results: Data was available for 197 ERCPs. Mean age at ERCP was 65.77 years. There were 47 (23.9%) ERCPs in Group A (mean age 86 years, range 81–97), and 150 (76.1%) in Group B (mean age 57 years, range 18–80). The indications and complications for procedures are demonstrated in Table 1. There were a total of 28 complications, 8 (17.0%) in Group A, and 20 (13.3%) in Group B. There was no significant difference in total complication rates between the 2 groups (Fisher's exact 2-tailed test, p = 0.63). Similarly, no significant differences were identified in specific complications between Group A and B (2-tailed Fisher's exact test): bleeding (p = 1.00), pancreatitis (p = 0.63), biliary sepsis (p = 1.00), perforation (p = 1.00), others (p = 0.20). There were no in-hospital deaths directly related to ERCP in either age group (p = 1). Conclusion: There was no increase in procedural complication rates or mortality in elderly patients undergoing ERCP in our study population. Our data adds weight to the growing evidence that ERCP is a safe and well tolerated procedure in the elderly. Disclosure of Interest: None Declared